Pharmacotherapy for Atrial Fibrillation in Patients With Chronic Kidney Disease: Insights From ORBIT‐AF - Jeffrey B. Washam; DaJuanicia N. Holmes; Laine E. Thomas; Sean D. Pokorney; Elaine M. Hylek; Gregg C. Fonarow; Kenneth W. Mahaffey; Bernard J. Gersh; Peter R. Kowey; Jack E. Ansell; Alan S. Go; James A. Reiffel; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Chronic kidney disease (CKD) is a common comorbidity in patients with atrial fibrillation. The presence of CKD complicates drug selection for stroke prevention and rhythm control. Methods and Results Patients enrolled in ORBIT AF (Outcomes Registry for Better Informed Treatment of Atrial Fibrillation) with baseline renal function and follow‐up data were included (N=9019). CKD was defined as an estimated creatinine clearance <60 mL/min. Patient characteristics were compared by CKD status, and Cox proportional hazards modeling was used to examine the association between oral anticoagulant (OAC) use and outcomes and antiarrhythmic drug use and outcomes stratified by CKD stages. At enrollment, 3490 (39%) patients had an estimated creatinine clearance <60 mL/min. Patients with CKD were older and had higher CHA2DS2VASc and Anticoagulant and Risk Factors in Atrial Fibrillation (ATRIA) scores. A rhythm control strategy was selected less frequently in patients with CKD, while OAC use was lower among Stage IV and V CKD patients. After adjustment, no significant interaction was noted for OAC and CKD on all‐cause mortality (P=0.5442) or cardiovascular death (P=0.1233), although a trend for increased major bleeding (P=0.0608) and stroke, systemic embolism or transient ischemic attack (P=0.0671) was observed. No interaction was noted for antiarrhythmic drug use and CKD status on all‐cause mortality (P=0.9706), or stroke, systemic embolism or transient ischemic attack (P=0.4218). Conclusions Patients with atrial fibrillation and CKD are less likely to be treated with rhythm control. Patients with advanced CKD are less likely to receive OAC. Finally, outcomes with OAC in patients with advanced CKD may be materially different with higher rates of both bleeding and stroke.